Syntheses, silylation, characterization, and antimicrobial and antifertility activities of organoboron derivatives of some bioactive monofunctional bidentate semicarbazones. (11th August 2017) - Bhomia, Jyoti; Sharma, Jyoti; Lakhne, Rucha; Sharma, Rachna; Gupta, R.S.; Sharma, Ram Avatar; Singh, Yashpal
Abstract : Some new mononuclear organoboron derivatives of the type PhBL 1–5 (OH) (1a –1e ) were synthesized by the reaction of PhB(OH)2 and LH (LH = OC(NH2 )NH:NC(CH3 )4 C6 H4 R, where R = H (L 1 H); CH3 (L 2 H); OCH3 (L 3 H); Cl (L 4 H); Br (L 5 H)) in 1:1 molar ratio in refluxing tetrahydrofuran (THF). This was followed by the reactions of PhBL 1–5 (OH) with NH(SiMe3 )2 in 2:1 molar ratio in THF to yield new heterodinuclear derivatives of the type PhBL 1–5 (OSiMe3 ) (2a –2e ). All these newly synthesized complexes were characterized using elemental analyses and their probable structure was proposed on the basis of infrared, 1 H NMR, 13 C NMR, 11 B NMR and 29 Si NMR spectral data and mass spectrometry. Semicarbazone ligands and their corresponding mono‐ and heterodinuclear boron derivatives were screened against pathogenic bacteria ( E. coli and P. aeruginosa ) and fungi ( A. niger and P. peniculosum ) to examine their antimicrobial activities. Representative compounds of each series of mono‐ and heterodinuclear boron derivatives and a ligand were screened for their antifertility activity on male adult Wistar rats. Abstract : Antimicrobial and antifertility activities of semicarbazones and their corresponding mono‐ and heterodinuclear boron derivatives have been investigated with a view to examining their potential as drugs.